Corporate Identity and Armed Conflicts : Analysis of brand conduct in the invasion of Ukraine - Muñoz-Sastre, Daniel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
The way corporations behave on a daily basis is a key element when it comes to relating not only with their stakeholders, but also with the rest of the members of the society to which they belong. This fact is more noticeable in situations of great magnitude, as in the case of the COVID-19 pandemic or the invasion of Ukraine. This article analyzes the identity of some of the world's leading corporations and their actions in the face of this armed conflict.